The AI-cyber nexus: implications for military escalation, deterrence and strategic stability. Issue 3 (2nd September 2019) - Johnson, James
ABSTRACT: How could AI-infused cyber capabilities be used to subvert, or otherwise compromise, the reliability, control and use of states' nuclear forces? This article argues that a new generation of artificial intelligence (AI) enhanced cyber capabilities will amplify the risk of inadvertent escalation caused by the co-mingling of nuclear and strategic non-nuclear weapons and the increasing speed of warfare, thereby increasing the risk of nuclear confrontation. It examines the potential implications of cyber (offensive and defensive) capabilities augmented with AI applications for nuclear security. The article concludes that future iterations of AI-enhanced cyber counterforce capabilities will complicate the existing challenges of cyber defence, and in turn, compromise nuclear assets and increase the escalatory effects of offensive cyber capabilities.